Efficacy of Rhazya stricta leaf and seed extracts against Rhyzopertha dominica and Trogoderma granarium - Alvi, Abid Mahmood; Iqbal, Naeem; Bashir, Muhammad Amjad; Rehmani, Muhammad Ishaq Asif; Ullah, Zabbeh; Latif, Abdul; Saeed, Qamar (Kuwait Journal of Science, 2018)
The protection of stored grains from insect pests depends upon highly toxic synthetic insecticides which cause a number of harmful effects on public health and environment. This necessitates finding eco-friendlier control measures of these stored insects pests. In this study, leaf and seed extracts of the local medicinal plant Rhazya stricta (Apocynaceae) were evaluated for toxicity and repellency to Rhyzopertha dominica (Coleoptera: Bostrichidae) and Trogoderma granarium (Coleoptera: Bostrichidae) under laboratory conditions. The results show an increase in mortality (%) and repellency (%) with an increase in the concentrations of the extracts. After 120 h, the leaf extract caused the highest mortality (61.10 ± 1.20 - 72.11 ± 1.25%) as compared to the seed extract (56.95 ± 3.26 - 69.50 ± 1.04) in both targeted insects. Leaf and plant extracts show maximum repellency (62.50 ± 1.73 - 47.20 ± 1.45%) in R. dominica and T. granarium at higher concentrations in comparison to lower concentration in the 24-hour trial. Our study suggests that leaf extracts of the medicinal plant R. stricta could be used as an effective component of the integrated pest management program against stored grain pests.